2013
DOI: 10.1042/bj20130342
|View full text |Cite
|
Sign up to set email alerts
|

Elevated SGK1 predicts resistance of breast cancer cells to Akt inhibitors

Abstract: The majority of human cancers harbour mutations promoting activation of the Akt protein kinase, and Akt inhibitors are being evaluated in clinical trials. An important question concerns the understanding of the innate mechanisms that confer resistance of tumour cells to Akt inhibitors. SGK (serum- and glucocorticoid-regulated kinase) is closely related to Akt and controlled by identical upstream regulators {PI3K (phosphoinositide 3-kinase), PDK1 (phosphoinositide-dependent kinase 1) and mTORC2 [mTOR (mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(167 citation statements)
references
References 39 publications
7
158
0
Order By: Relevance
“…Interestingly, two of these lines, MDA-MB-157 and MDA-MB-436, were not responsive to AZD5363. SGK-1 expression activation has recently been shown to be associated with reduction in sensitivity to AKT inhibition in breast cancer cell lines (18). Although a relationship is seen as expected between SGK-1 expression and sensitivity to AZD5363, the relationship is not as clear for AZD8186 (Fig.…”
Section: Azd8186 Inhibits Akt Pathway Activation and Growth Of Multipmentioning
confidence: 62%
“…Interestingly, two of these lines, MDA-MB-157 and MDA-MB-436, were not responsive to AZD5363. SGK-1 expression activation has recently been shown to be associated with reduction in sensitivity to AKT inhibition in breast cancer cell lines (18). Although a relationship is seen as expected between SGK-1 expression and sensitivity to AZD5363, the relationship is not as clear for AZD8186 (Fig.…”
Section: Azd8186 Inhibits Akt Pathway Activation and Growth Of Multipmentioning
confidence: 62%
“…Interestingly, our findings are also consistent with data suggesting that SGK-1 activity can mediate the sensitivity of cancer cells to targeted therapies. 34 It is noteworthy that other investigators have discovered that SGK-1 can interact with proteins at the mitochondria and can inhibit the induction of necrotic cell death. 19,35 Our data implicating SGK-1 in ATP generation may provide additional insight into these connections between SGK-1 and mitochondrial integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Response of pNDRG1 to AKT inhibition in breast cancer cell lines is variable. Some cell lines respond to AKT inhibition with a decrease in NDRG1 phosphorylation, whereas others do not (18). We found that NDRG1 phosphorylation was suppressed in cells treated with inhibitors of PI3K (BKM120, BYL719, PIK75, and TGX221) and AKT (MK2206 and GSK650394) but not inhibitors of PARP (Olaparib) or MAPK (GSK112021), i.e., we found that NDRG1 phosphorylation in HCC1937 cells was responsive to PI3K and AKT inhibition, confirming these previous reports of cross-talk between PI3K, AKT, and mTOR signaling (but excluding ERK signaling) with regard to SGK activity.…”
Section: Pi3kmentioning
confidence: 99%